Proceedings of the 3rd ACM International Conference on Systems for Energy-Efficient Built Environments 2016
DOI: 10.1145/2993422.2993582
|View full text |Cite
|
Sign up to set email alerts
|

Data Predictive Control for Peak Power Reduction

Abstract: Decisions on how best to optimize today's energy systems operations are becoming ever so complex and conflicting such that model-based predictive control algorithms must play a key role. However, learning dynamical models of energy consuming systems such as buildings, using grey/white box approaches is very cost and time prohibitive due to its complexity. This paper presents data-driven methods for making controloriented model for peak power reduction in buildings. Specifically, a data predictive control with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Step 2: Linear regression models are trained in the leaves (or terminal nodes) of the trees which are function of only X c . We have validated this linear model assumption in [10]. As we shall see in Sec.…”
Section: A Separation Of Variablesmentioning
confidence: 65%
See 1 more Smart Citation
“…Step 2: Linear regression models are trained in the leaves (or terminal nodes) of the trees which are function of only X c . We have validated this linear model assumption in [10]. As we shall see in Sec.…”
Section: A Separation Of Variablesmentioning
confidence: 65%
“…In our previous work [9], [10], we introduced the concept of DPC for receding horizon control. This work has the following contributions.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this complexity above, the regression treebased approaches were employed in the literature to develop data-driven predictive models. Authors in [30,31] developed RT and random forest for building control in different settings. However, the simulation results demonstrated that these models were trapped in limitations due to overfitting and high variance [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, developing a learning based approach for the optimal DR strategies and the relevant model can be learned through the historical data, which is urgent and attractive. Some recent literature has paid attention to the study based on the learning method [18][19][20][21][22][23][24][25]. For example, in [18], a model based control with a regression trees method was exploited for optimal DR strategies for large commercial buildings.…”
Section: Introductionmentioning
confidence: 99%